Simulasi Numerik Prarancangan Perpipaan LNG Circulation Line di Aliran Masuk Air Ambient Vaporizer (AAV) - Muhammad Ikhsan; Ratna Sari; Reza Fauzan (Jurnal Teknologi, 2023)
The circulation process is a process to make pipes in the LNG industry always in LNG operational cryogenic temperature condition -160° C. The LNG circulation line facility on the AAV inlet pipe is expected to flow LNG continuously as a solution to keep the pipe always in a state of cryogenic temperature. The pressure drop from one point to another with lower pressure is referred to as a "pressure drop. Loss of pressure in the process at the AAV piping system is caused by several parameters including pipe size, flow rate, and pressure also because of a change in pipe size and friction along the pipeline. The purpose of this research is to analyze the effect of pipe size on pressure drop and compare it with theoretical calculations and simulation programming. Hysys is engineering software designed to simulate processes in industry to design process calculations related to engineering. Based on the results of the manual calculation, the 3-inch pipe size has the lowest pressure drop value of 0.314 kg/cm2 and the results using aspen hysys is 0.053 kg/cm2. Using a double pipe piping system, the 4-inch annulus has a pressure drop value of 0.445 kg/cm2, and the result from Aspen Hysys is 0.059 kg/cm2. Pressure drop is significantly influenced by pipe size; the smaller the pressure drop that happens, the greater the pipe size must match the pipe connection size. The pressure drop that occurs in variations in pipe size has a great influence on the LNG flow back into the storage tank.